Applying citizen science to water security challenges in Ethiopia: a structured approach - Haile, Alemseged Tamiru; Tedla, H. Z.; Mengistie, G. K.; Gebre, E. S.; Nigussie, Likimyelesh; Haileslassie, Amare; Nicol, Alan (International Water Management Institute, 2025)
Citizen science (CS) is an important approach to involve the public in scientific research and contribute to addressing water security issues. CS programs, led by the International Water Management Institute (IWMI) and local partners in Ethiopia, meaningfully engage communities in data collection and knowledge co-generation. However, challenges such as limited resources, data quality issues and lack of awareness among decision-makers highlight the need for training, sustained funding and alignment with local problems. The technical brief emphasizes the importance of leveraging CS to fill hydrometeorological monitoring gaps, ensuring data accuracy and community engagement, and developing frameworks for expanding CS programs. By aligning with community needs and fostering inclusive participation, CS can strengthen water security initiatives in Ethiopia, creating a foundation for sustainable and locally relevant solutions to water management.